The Impact of Geometry Engineering on Combustion Efficiency and Emissions: Performance Evaluation of Axial Diffuser Tube, Perforated Distribution Node, and Symmetrical Axial Radiator - Jameel Al-Naffakh; Mohammed R. Al-Qassab; Abdulhussein H.J; Israa Jafar Jafar (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
With increasing environmental concerns about emissions, improving combustion systems for alternative fuels, such as used engine oil, has become imperative. Investigating innovative burner designs to enhance fuel-air mixing, reduce emissions, and stabilize performance presents challenges due to high viscosity and incomplete combustion. However, previous research has not adequately addressed the role of burner head geometry in mitigating these problems. A combination of experimental tests and computational fluid dynamics (CFD) simulations was used to evaluate the performance. This study aims to fill the gap by evaluating the effects of three burner head designs—axial diffuser tube, perforated distribution node, and symmetrical axial cooler—on combustion efficiency and emissions. The results indicate that the axial diffuser tube achieved the highest efficiency (94.3%) and lowest emissions (NOx: 128 ppm, CO: 52 ppm, PM: 18 μg/m3) due to uniform heat distribution and increased turbulence. The perforated distribution node showed a balanced performance, with an efficiency of 91.7% and moderate emissions (NOx: 145 ppm, CO: 65 ppm, PM: 24 μg/m³). Meanwhile, the symmetric axial cooler, designed for thermal stability, showed lower efficiency (89.6%) and higher emissions (NOx: 167 ppm, CO: 78 ppm, PM: 30 μg/m³). The results indicate the importance of burner engineering in balancing efficiency and emissions control. The results of this study support sustainable combustion technologies for industrial and domestic applications, and underscore the global transition to clean energy solutions. Keywords: Burner head design, CFD simulations, Combustion efficiency, Emissions reduction, Geometric engineering, Waste automotive oil.